Copper Toxicity of Four Different Aquaculture Ponds - Moshood Mustapha; Joshua Taiwo Agunloye (Journal of Tropical Life Science, 2016)
> Copper is a nutritional trace element for fish which could be deficient or toxic. Copper concentrations from four aquaculture ponds were analyzed for 12 weeks using Bicinchoninate method. Alkalinity was measured using colorimetric method with the aid of Hanna Multiparameter Bench Photometer. Temperature and pH of the ponds was measured in situ using Hanna Portable pH/EC/TDS/Temp combined waterproof tester. All measurementswere done I triplicates. Copper concentrations ranged from 0.01 to 0.10 mg/L, alkalinity ranged from 105 to 245mg/L. Weeks 1 and 12 recorded the highest and lowest Cu2+ concentrations, while lowest and highest alkalinity were obtained in weeks 1 and 12 respectively in all the ponds. Temperature and pH ranged from 29.1 to 35.9Â°C and 6.35 to 8.03. The trend of copper concentrations in the ponds was Natural > Earthen > Concrete > Collapsible, with concentration slightly above the normal in the ponds. This could have come from the pipes used in delivering water to the pond, copper alloy nets and mesh used in the ponds, anti-fouling agents, algaecides, water source and fish meal. Effect of elevated copper was seen in the morphology and behavior of Clarias gariepinus which include slimy mucus on the skin, aggressive and uncoordinated swimming with the opercula flared, slow growth, reduced odor perception of food and water bubbles on the ponds. Copper should be regularly bio monitored to determine toxicity in fish.